2021
DOI: 10.1177/14574969211042455
|View full text |Cite
|
Sign up to set email alerts
|

Does minimally invasive liver resection improve long-term survival compared to open resection for hepatocellular carcinoma? A systematic review and meta-analysis

Abstract: Introduction: Minimally invasive liver surgery for hepatocellular carcinoma has gained widespread interest as an alternative to conventional open liver surgery. However, long-term survival benefits of this approach seem unclear. This meta-analysis was conducted to investigate long-term survival following minimally invasive liver surgery. Method: A systematic review was performed to identify studies comparing long-term survival after minimally invasive liver surgery and open liver surgery until January 2020. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Another multicenter study showcased a significant trend in robotic liver resection, indicating improved disease-free survival and overall survival when compared to open surgery [44]. These data have been confirmed by several updated meta-analyses [51][52][53][54][55], which conclude that MILS improves short-term and long-term oncological outcomes.…”
Section: Does Mils Improve Post-resection Outcomes?mentioning
confidence: 77%
“…Another multicenter study showcased a significant trend in robotic liver resection, indicating improved disease-free survival and overall survival when compared to open surgery [44]. These data have been confirmed by several updated meta-analyses [51][52][53][54][55], which conclude that MILS improves short-term and long-term oncological outcomes.…”
Section: Does Mils Improve Post-resection Outcomes?mentioning
confidence: 77%
“…This effect remains unclear, but it has also been observed in other patient cohorts, such as cirrhotic patients. Indeed, a meta-analysis of more than 4000 patients operated on in VL for hepatocarcinoma showed a reduction in 5-year all-cause mortality [ 20 ]. Another systematic review showed that a reduction in postoperative complications has a long-term effect on both OS and DFS [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…After the groups were matched, we ran a diagnostic balancing analysis to see how well they matched. We opted to run regression models in which we additionally adjusted the impact for the same covariates of matching variables because the balance of matching was not ideal (one to one) for each variable [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…At present, solitary lesions (≤5 cm) located in segments 2 through 6, which was the most acceptable LLR indication, as well as laparoscopic major liver resection, have been performed [7,8,14,[16][17][18][19][20]. With these LLR developments, perioperative outcomes are better in patients with HCC who underwent LLR than those who underwent OLR, with no difference in long-term outcomes [16,17,[21][22][23], whereas a recent systematic review and meta-analysis study indicated better long-term outcomes after minimal invasive liver resection (MILR), including LLR (48 articles) and robot-assisted liver resection (RALR, 2 articles) for HCC than OLR among the recently published data [24]. The pooled analysis revealed an 18% decrease in diseasespecific 3-year mortality after MILR (almost, LLR) compared with OLR (Figure 1), and the sensitivity analysis of contemporary studies from 2010 to 2019 revealed a significantly lower 5-year all-cause mortality and 3-year disease-specific mortality in MILR compared to OLR.…”
Section: Introductionmentioning
confidence: 99%
“…The studies shown in this figure can be found as references[6,21,23,. Reprinted/adapted with permission from Ref [24]…”
mentioning
confidence: 99%